2018
DOI: 10.1364/josaa.35.00b287
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an impact of melanopsin activation on unique white perception

Abstract: Current models of human color vision only consider cone inputs at photopic light levels, yet it is unclear whether the recently discovered melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs) contribute to color perception. Using a lab-made five-primary photostimulator that can independently control the stimulations of rods, cones, and ipRGCs in human retina, we determined the observer’s unique white perception, an equilibrium point for signals arising from the opponent mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
2
36
0
1
Order By: Relevance
“…A body of data suggest that the signal of ambient light provided by melanopsin is used to adjust aspects of conventional cone-based vision 1521 . However, experiments in both mice and humans indicate that melanopsin can also influence perception more directly, by providing a sense of ‘brightness’ 12,14,22 (and perhaps in other ways 23 ). For technical reasons, melanopsin-driven perception has, thus far, been studied only with diffuse and/or large featureless stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…A body of data suggest that the signal of ambient light provided by melanopsin is used to adjust aspects of conventional cone-based vision 1521 . However, experiments in both mice and humans indicate that melanopsin can also influence perception more directly, by providing a sense of ‘brightness’ 12,14,22 (and perhaps in other ways 23 ). For technical reasons, melanopsin-driven perception has, thus far, been studied only with diffuse and/or large featureless stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The second possibility is the influence of rods and ipRGCs in color appearance. It has been shown that ipRGCs have a visual impact on peripheral vision 39 43 . However, the subtypes of ipRGCs, M2 and M4, which innervate dLGN 44 , also exist in the fovea 45 , suggesting that ipRGCs affect color perception even in the fovea.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study and a recent one [17] employing a similar system find that non-visual responses can be manipulated with a modified VDU with more than three primaries. Additionally, there is more and more evidence that melanopsin contributes to “classical” visual functions such as the perception of brightness [22, 42], colour [9, 43], space (humans: [9]; mice: [44, 45]), contrast [46, 47], and other visual attributes (humans: [24], mice: [4850]). It remains an interesting question to what extent the classical colour matching functions, which are the basis of our current cone fundamentals, reflect the activity of melanopsin (though the amount of rod contributions have been discussed extensively [51]).…”
Section: Discussionmentioning
confidence: 99%